Assessment of Physico-Chemical Parameters of Water Samples Collected from the Southern Part of Bangladesh (Dhaka University Journal of Science, 2022)
Bangladesh has a vast natural water resources. In order to determine the water quality parameters such as pH, EC, DO, BOD, TOC, ionsi.e., NO3-, SO42-, PO43- and heavy metals, thirty surface water samples were collected from the southern part of Bangladesh includingthe coastal regions of Patuakhali district and Kuakata sea beach area during the dry season. The pH of water samples was ranged from7.58 to 8.77 with an average of 8.15. The average conductivity value was 8.83±2 mS/cm. The average DO was 8.33±1.82 mg/L andBOD was 0.31±0.03 mg/L. TOC was found between 0.78 and 1.78 mg/L with an average of 1.24 mg/L. The concentration of NO3-,SO42-, PO43- was determined by ion chromatography and only sulphate ion was detected in a very low concentration. Water samplesfrom different sources were analysed for five metals by AAS and the concentrations of Pb, Cd, Mn, Hg and As were below 0.2, 0.01,0.22, 0.001 and 0.005 mg/L, respectively.Dhaka Univ. J. Sci. 70(1): 49-57, 2022 (January)